Importance of GPCR-Mediated Microglial Activation in Alzheimer’s Disease - Haque, Md. Ezazul; Kim, In-Su; Jakaria, Md.; Akther, Mahbuba; Choi, Dong-Kug (Frontiers in Cellular Neuroscience, 2018)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder associated with impairment of cognition, memory deficits and behavioral abnormalities. Accumulation of amyloid beta (Aβ) is a characteristic hallmark of AD. Microglia express several GPCRs, which, upon activation by modulators, mediate microglial activation and polarization phenotype. This GPCR-mediated microglial activation has both protective and detrimental effects. Microglial GPCRs are involved in amyloid precursor protein (APP) cleavage and Aβ generation. In addition, microglial GPCRs are featured in the regulation of Aβ degradation and clearance through microglial phagocytosis and chemotaxis. Moreover, in response to Aβ binding on microglial Aβ receptors, they can trigger multiple inflammatory pathways. However, there is still a lack of insight into the mechanistic link between GPCR-mediated microglial activation and its pathological consequences in AD. Currently, the available drugs for the treatment of AD are mostly symptomatic and dominated by acetylcholinesterase inhibitors (AchEI). The selection of a specific microglial GPCR that is highly expressed in the AD brain and capable of modulating AD progression through Aβ generation, degradation and clearance will be a potential source of therapeutic intervention. Here, we have highlighted the expression and distribution of various GPCRs connected to microglial activation in the AD brain and their potential to serve as therapeutic targets of AD.